1985
DOI: 10.1161/01.hyp.7.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in experimental diabetes mellitus. Renin-prostaglandin interaction.

Abstract: SUMMARY To investigate mechanisms involved in the high incidence of hypertension in diabetes mellitus, the relationship between renin-angiotensin production and renal prostaglandin E 2 synthesis was studied in rats 1 week after diabetes mellitus had been induced by streptozotocin injection. The diabetic rats became hypertensive, although plasma renin activity did not increase despite the plasma volume contraction resulting from polyurla and natriuresis. Subcutaneous insulin injection resulted in a marked incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…Christlieb [29] found that severely hyperglycemic rats had lower levels of renin than normal or moderately hyperglycemic ani mals. This has been verified by others [30,31,33], Severe hyperglycemia will likely lead to volume depletion, which in turn should stimulate renin secretion. This does not occur, however.…”
Section: Experimental Diabetessupporting
confidence: 55%
“…Christlieb [29] found that severely hyperglycemic rats had lower levels of renin than normal or moderately hyperglycemic ani mals. This has been verified by others [30,31,33], Severe hyperglycemia will likely lead to volume depletion, which in turn should stimulate renin secretion. This does not occur, however.…”
Section: Experimental Diabetessupporting
confidence: 55%
“…These changes may reflect the decline in cardiac function that arises during this stage of the disease (49). In contrast, some groups have reported no change (50,51) or an increase in BP in diabetic rats (52). It is possible that the discrepancies in these studies may be due to differences in the severity or the duration of diabetes, use of anesthetics, or method of BP measurement.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies from our own laboratory have shown lower HR and reduced systolic blood pressure in conscious STZ-induced diabetic rats (44). However, a few studies from other laboratories have reported unchanged (5,6,24) or increased blood pressure in diabetic rats (22). Although the reasons for these discrepancies are not very clear, it is likely that differences in the duration of diabetes, use of anesthetics, and varied techniques employed for measurement of blood pressure may have contributed to the disparities in the observed results (25).…”
Section: Discussionmentioning
confidence: 98%